Computer simulation of the last support phase of the long jump - Chow, J. W.; Hay, J. G. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The purpose was to examine the interacting roles played by the approach velocity, the explosive strength (represented by vertical ground reaction force [VGRF]), and the change in angular momentum about a transverse axis through the jumper's center of mass ([delta]Hzz) during the last support phase of the long jump, using a computer simulation technique.